Effect of IV ferric carboxy maltose for moderate/severe anemia: a systematic review and meta-analysis - Mahalaqua Nazli Khatib; Anju Pradhan Sinha; Shilpa Gaidhane; Shilpa Upadhyay; Nikita Waghmare; Abhishek Anil; Deepak Saxena; Shailendra Sawleshwarkar; Padam Prasad Simkhada; Abhay Gaidhane; Zahiruddin Syed Quazi (Frontiers in Medicine, 2024)
IntroductionAnemia remains a prevalent global health issue with varying severity. Intravenous iron supplementation, particularly with ferric carboxymaltose (FCM), has appeared as a possible therapeutic intervention for individuals with moderate to severe anemia. The study aimed to assess the efficacy and safety of ferric carboxymaltose (FCM) in reducing anemia.MethodsWe searched electronic databases, registries, websites, e-libraries, reference lists of reviews, citations, etc. We included randomized control trials (RCTs), non-RCTs, and single-arm studies, while observational studies, case series, and case studies were excluded. Two reviewers independently screened the studies and extracted the data. We included studies of moderate-to-severely anemic Indians and excluded Indians with other comorbidities. We assessed the risk of bias and the overall quality of evidence (QoE) using GRADE GDT.ResultWe identified 255 studies and included 14 studies (11 RCT, one non-RCT, and two single-arm studies) with 1,972 participants for qualitative analysis and 10 studies in the meta-analysis. All the included studies detailed the use of FCM for anemia. The primary outcomes assessed in the included studies were anemia, hemoglobin, and adverse events. The outcomes assessed ranged from 2 weeks to 12 weeks. The risk of bias varied across different studies with different outcomes. FCM is consistent with a fewer number of adverse events as compared to other interventions and provides “moderate” to “very low” QoE.ConclusionA slow single infusion of 1 gram of FCM is well-tolerated, safe, and effective in treating iron deficiency anemia (IDA) and surpasses other interventions (Iron Sucrose Complex (ISC), Iron sucrose, and ferrous ascorbate) in elevating hemoglobin levels and replenishing iron stores.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=459363, CRD42023459363.